从勒菲弗尔三要素理论理解翻译者的文化背景和目标读者的文化影响翻译 ：以比较两本《论语》的英译本為例 = Understanding translator’s cultural background and receiving culture affects translation from the perspective of Lefebvre’s three-factor theory : a comparative study of two English-translated analects works - Tham, Mavis (2016)
上世纪 90 年代，西方翻译理论界出现了“文化转向”。其中，勒菲弗尔翻译操控理论就是翻译研究“文化转向”下的一个重要理论。该理论主要探讨翻译在什么样的文化背景下产生，以及译作给译入语文化带来的影响。安德烈·勒菲弗尔是翻译操控论的一面旗手，他对这一理论的形成以及完善做出了重要贡献。勒菲弗尔将翻译视为对原作的改写，是对原作“操控”，打破了以原文作为标准评价翻译的传统思维。他指出翻译不能真实地反映原文的风貌，主要是因为它始终受到三大因素的操纵:意识形态、诗学观和赞助人的力量。本文借重当代翻译研究学派重要学者安德烈·勒菲弗尔的制约翻译与改写的三要素理论，通过对中国古代重要文化典籍《论语》的两个英译本(辜鸿铭译本,埃德拉·庞德译本) 的比较研究，从两个译本的译文特色探讨影响《论语》英译的重要力量及其表现。通过两个译本的对比研究发现，辜鸿铭和庞德在翻译论语时都分别受到了意识形态,诗学规范和赞助人不同程度的影响。从意识形态层面来看，辜鸿铭受到原语晚清时期社会主流意识的影响，选择向西方译介论语，从文化层面改变西方社会上层人士对中国文化的重新认识，实现爱国救民的根本目的；庞德受到 二十世纪初世界大战和经济危机的混乱社会秩序的影响，选择英译论语，企图从东方儒学经典中追寻根治西方资本主义文明的弊病。从诗学层面来看，辜鸿铭受到目的语诗学的影响，译文选材主题符合维多利亚时期文学的道德教诲功能；庞德受到他所倡导的意象主义诗学运动的主张，译文简洁，融入意象。从赞助人层面来看, 辜鸿铭和庞德在翻译论语时所受到赞助人的影响非常有限。两位译者在翻译论语时，主要受到不同时代意识形态和诗学因素的影响，译本呈现出不同的特点。而这些都是因为演绎着的文化背景。辜鸿铭的论语翻译主要受到了意识形态的影响，译文呈现出以下特点：为了让西方读者接受并理解论语思想，达到儒家文化在西方的传播改变西方上层人士对中国的认识，采取了归化的翻译策略；在文化的翻译处理上，尽量删除中国的专有名词，引用西方读者熟悉的作家学者，便于西方读者理解论语思想。庞德在英译论语时，受到意识形态的影响，企图抓住论语的精髓，采取了异化的翻译策略。然而，诗学是操控庞德论语英译的重要力量，他主要受到意象主义诗歌创作三原则的影响，译文呈现出句式简洁，措词融入意象，口语体的押韵格律的显著特色。所以不管是收到意识形态或诗学的影响，都是翻译者被当时的文化所影响，二爷影响了翻译作品。Manipulation theory, which arose in 1990s, is a representative of the cultural change in western translation study world. It mainly explores the cultural background in which translation is produced and the influences that translated work brings to the receiving culture. André Lefevere, as the initiator of this theory, contributes a lot to the formulation and improvement of the study of translational manipulation theory. He proposes that translation is rewriting and manipulation in essence and further generalized three key factors which govern and manipulate one’s translation: ideology, poetics and patronage. In the present thesis, Andre Lefevere's Three-Factor Theory is applied to the comparative study of two English versions of the great Chinese classic the Analects respectively by Ku Hung Ming and Ezra Pound. Through the comparative study of two translations, the author attempts to reveal the three manipulative forces embodied specifically in each version and the most affective force in each translation. Based on the study, it is drawn that Ku Hung Ming and Ezra Pound were manipulated respectively by the three affecting factors (ideology, poetics and patronage) when they were doing the translation of the Analects. In terms of the impact of ideology, under the influences of the social dominant ideology of the original text in the Late-Qin Period, Ku Hung Ming determined to translate the Analects and introduce the Confucian thoughts to the West with the purpose of changing the Western glitterati’s attitude to Chinese culture and saving the declining China in cultural level; Influenced by the chaotic world order caused by the world wars and financial depression at the first half of 20th century, Pound chose to translate the Analects in the hope of seeking the cure to eradicate the ills deeply rooted in the Capital Civilization from the Confucianism in the East. In terms of the impact of poetics, influenced by the literary function (Moral Enlightenment) in the target language in the Victorian Age, Ku Kung Ming chose to translate The Analects and his translation corresponds with the literary criterion in the receiving culture; However, Pound’s translation is concise and rich in poetic and pictorial splendor due to the manipulation of the poetics of the Imagism Movement he actively pioneered. In terms of the impact of patronage, the two rewriters were relatively free from the constraints of patronage，however the receiving culture have affected their translations. Without wanting to reach targeted audience, they have to translate their work for the intended audience to understand. The two translations were mainly manipulated by different ideologies and poetics in the different periods and have different features. This shows that translators are always affected and manipulated by the cultural background of that period. Among the three factors, ideology is most influential to Ku Hung Ming’s translation whereas poetics exerts the greatest impact on Pond’s translation. Influenced by his ideology, Ku Hung Ming formed his own translation purpose: changing the Western intellectuals’ attitudes to Chinese culture and saving the declining China in cultural level. In order to get Western readers understand Confucian thoughts expressed in The Analects, he adopted the strategy of Domestication” and used unique ways of dealing with “Universe of Discourse” such as the deletion of Chinese Proper names and a lot of quotations from famous European writers. Under the influences of his ideology, Pond adopted the translation strategy of “Foreignization” in order to catch the essence of the Confucianism in the original text. However, the factor of Poetics is the most important force manipulating Pond’s translation. Following the three Imagist poetic principles in writing, he adopted succinct sentence patterns and a diagrammatic method to render Chinese characters, creating a vivid image for English readers. Therefore, his translation is quite like a poem, characteristic with visual image and brevity. Both Ku Hung Ming and Pond creatively translated The Analects. Having been manipulated by different ideologies and poetics in the different periods, their translations are distinct in style with sharp epochal feature. This thesis further corroborates Lefevere’s Manipulation Theory and in the meantime, it provides a theoretical and practical basis for the literature translation criticism in the future.